Vogt-Koyanagi-Harada disease and bilateral simultaneous Adie’s pupil - Akter, Most. Sanjida; Mehbub Ul Kadir, Syeed; Shultana, Razia; Rahman, Sarwat; Rahman, Md. Zahedur; Maurya, Rajendra Prakash (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2024)
Vogt-Koyanagi-Harada (VKH) syndrome is an uncommon autoimmune inflammatory malady commonly accompanied by neurological, auditory, and integumentary signs. We report a case of a teenage girl who complained of persistently decreased vision for the last 15 days. There was no systemic association. After 2 weeks, the patient developed tonic pupils. The pupil showed a tonic response to a 0.125% pilocarpine eye drop. Upon examinations, the patient was diagnosed with Vogt-Koyanagi-Harada disease and bilateral Adie’s pupil, which is a rare conditions associated with VKH disease. Early treatment is crucial for preserving vision.